THE ISRAEL-IRAN CYBER WAR: THE DIGITAL DIMENSION OF MIDDLE EASTERN CONFLICTS IN A POST-UNIPOLAR WORLD - Bogićević, Aleksandar (The Policy of National Security, 2026)
The conflict between Israel and Iran represents one of the most enduring confrontations in the Middle East. Over the past decade, its dynamics have increasingly been characterised by multidimensionality, reflected in the spillover of the conflict beyond traditional military-political frameworks into other domains, including the digital sphere. Following the Israeli Stuxnet attack on Iranian nuclear infrastructure in 2010, the cyber field has become a pivotal arena of confrontation, involving not only Israel and Iran but also affiliated cyber actors, often operating from third-party states, which adds a further layer of unpredictability and complexity to the conflict. What makes this cyber confrontation particularly significant for interstate relations in the highly sensitive Middle East is the ability of states to inflict damage on one another without resorting to armed force. On a global scale, this conflict reflects a broader transformation of relations between major actors in the international order. The support provided to Israel by the United States, coupled with the growing cooperation of Russia and China with Iran, indicates that the Iranian-Israeli cyber war is becoming an integral part of global geopolitical competition. This research aims to analyse cyber warfare between Israel and Iran, its role in their broader conflict, and its effects on both states and the regional actors who, due to their interconnectedness and complex mutual relations, also become targets. The author highlights the growing importance of the cyber dimension as a field of competition in the Middle East, where “old conflicts” are taking on a new form by shifting the struggle into the digital space, making it an inseparable part of the region's contemporary geopolitical reality in a post-unipolar world.
Keywords: Israel; Iran; Cyber warfare; Cybersecurity; Middle East